DONALD TRUMP AND HIS SPEECH: A STUDY OF DIFFERENT USAGES OF DEIXIS - Spencer, Wildhan Randy; Jayantini, I Gusti Agung Sri Rwa; Suastini, Ni Wayan (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2021)
The present research focuses on different usages of deixis by Donald Trump in his speech on 1 June 2020 at Rose Garden, White House. The aim of this research is to analyze the use of deixis in Donald Trump’s speech. The descriptive qualitative method was used in analyzing the data found in this research. The collected data were analysed by observing how the deixis was used in sentences. In analyzing the data, Levinson’s (1983) theory about different usages of deixis was applied. Based on Levinson's theory of deixis usages, deixis can be used through a gestural, symbolic, and non-deictic way. This research found three ways of deixis usages in Donald Trump’s speech, namely gestural, symbolic, and non-deictic use. Symbolic way of deixis usage was the most frequent occurrence, that is 82 times. This finding was followed by the non-deictic usage which occurred 6 times, and gestural usage that occurred 3 times. By investigating the usage of deixis, this study is expected to give an understanding that in delivering a speech, deixis can be used in different ways to support the content meant to be shared by the speaker as well as to make effective message delivery.